The Neural Palette of Heme: Altered Heme Homeostasis Underlies Defective Neurotransmission, Increased Oxidative Stress, and Disease Pathogenesis - Adedamola Saidi Soladogun; Li Zhang (Antioxidants)
Heme, a complex iron-containing molecule, is traditionally recognized for its pivotal role in oxygen transport and cellular respiration. However, emerging research has illuminated its multifaceted functions in the nervous system, extending beyond its canonical roles. This review delves into the diverse roles of heme in the nervous system, highlighting its involvement in neural development, neurotransmission, and neuroprotection. We discuss the molecular mechanisms by which heme modulates neuronal activity and synaptic plasticity, emphasizing its influence on ion channels and neurotransmitter receptors. Additionally, the review explores the potential neuroprotective properties of heme, examining its role in mitigating oxidative stress, including mitochondrial oxidative stress, and its implications in neurodegenerative diseases. Furthermore, we address the pathological consequences of heme dysregulation, linking it to conditions such as Alzheimer’s disease, Parkinson’s disease, and traumatic brain injuries. By providing a comprehensive overview of heme’s multifunctional roles in the nervous system, this review underscores its significance as a potential therapeutic target and diagnostic biomarker for various neurological disorders.